MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA PESERTA DIDIK KELAS IV SD - Nurlev Avana; Tri Wera Agrita; Ratri Putri (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This research is based on the fact that teachers do not apply such models well. This leads to poor student learning processes and outcomes. This class action research aims to improve the results and process of learning mathematics in class IV SDN 34/II Leban. The study consists of two cycles: planning, implementation, observation, and reflection. The study begins in the second academic semester of 2022/2023. The data collection method is through observation, documentation, and test results. Research data analysis shows that a block-based learning model (PBL) can improve mathematical learning processes and outcomes in class IV SDN 34/II Lebanon. This is demonstrated by the teaching performance of teachers in cycle I of 74% and cycle II of 98%, with an increase in cycles I and II of 24%. Students learning performance in Cycle I was 64.22%, and Cycle II was 90.74%, with an increase in Cycle I & II of 26.5%. Student's learning performance at cycles 1 at 45.45% and cycles II at 72.72%, with increases in Cycluses I and 2 at 45.75%.